Squid industry by-product hydrolysate supplementation enhances growth performance of Penaeus monodon fed plant protein-based diets without fish meal - Pan, Maila V.; Cadiz, Rowena E.; Mameloco, Emelyn Joy G.; Traifalgar, Rex Ferdinand M. (Frontiers in Sustainable Food Systems, 2022)
Squid processing by-products were enzymatically hydrolyzed and used as a supplement in a plant protein-based diet, without fish meal, of Penaeus monodon to fully maximize the utilization of this marine resource. The hydrolysate was incorporated at 0, 0.5 and 1% levels in P. monodon diets containing 0 and 10% fish meal levels. Growth, digestive enzyme activities, muscle growth-, immune-related and gut pro-inflammatory gene expressions, and muscle morphometric measurements were evaluated as biological indices in an 8-week feeding trial. The squid by-product hydrolysate produced in the present study contains 90.25% protein, 5.84% lipid, 3.91% ash and has a molecular weight of 3.76 kDa. Supplementation at 1% hydrolysate in the experimental shrimp diet without fish meal resulted to the highest growth performance associated with increased feed intake, efficient feed and nutrient conversion and retention, enhanced digestive enzyme activities, up-regulation of muscle growth- and immune-related genes and suppression of the gut pro-inflammatory gene. The growth promotion is also linked with significant increase in muscle mean fiber area which suggests hypertrophic growth in shrimps. Generally, the supplementation of 1% squid by-product hydrolysate had supported the growth of P. monodon fed on a plant protein-based diet without fish meal.